Control of Adipocyte Differentiation in Different Fat Depots; Implications for Pathophysiology or Therapy - Ma, Xiuquan; Lee, Paul; Chisholm, Donald J.; James, David E. (Frontiers in Endocrinology, 2015)
Adipocyte differentiation and its impact on restriction or expansion of particular adipose tissue depots has physiological and pathophysiological significance in view of the different functions of these depots. Brown or “beige” fat [BAT] expansion can enhance thermogenesis, lipid oxidation, insulin sensitivity and glucose tolerance; conversely expanded visceral fat [VAT] is associated with insulin resistance, low grade inflammation, dyslipidaemia and cardiometabolic risk. The largest depot, subcutaneous white fat [WAT], has important beneficial characteristics including storage of lipid “out of harms way” and secretion of adipokines, especially leptin and adiponectin, with positive metabolic effects including lipid oxidation, energy utilisation, enhanced insulin action and an anti-inflammatory role. The absence of these functions in lipodystrophies leads to major metabolic disturbances. An ability to expand WAT adipocyte differentiation would seem an important defence mechanism against the detrimental effects of energy excess and limit harmful accumulation of lipid in “ectopic” sites, such as liver and muscle. Adipocyte differentiation involves a transcriptional cascade with PPARg being most important in WAT but less so in VAT, with increased angiogenesis also critical. The transcription factor, Islet1, is fairly specific to VAT and in vitro inhibits adipocyte differentiation. The physiological importance of Islet1 requires further study. Basic control of differentiation is similar in BAT but important differences include the effect of PGC-1a on mitochondrial biosynthesis and upregulation of UCP1; also PRDM16 plays a pivotal role in expression of the BAT phenotype. Modulation of the capacity or function of these different adipose tissue depots, by altering adipocyte differentiation or other means, holds promise for interventions that can be helpful in human disease, particularly cardiometabolic disorders associated with the world wide explosion of obesity.